Odpowiedzi

  • Użytkownik Zadane
2010-03-27T14:00:21+01:00
A)
a+a-b=2a +b

B)
2x-x-4=x-4

C)
7+x-6=x+1

D)
-x-4+x-5=-9

F)
y+2-2y-4=-y-2
Najlepsza Odpowiedź!
2010-03-27T14:04:48+01:00
A) a+(a-b) = a+a-b
b) 2x-(x+4) = 2x-x+4 =x +4
c) 7-(-x+6)= 7-x -6 = x + 7-6
d) -(x+4)+(x-5) = -x -4 +x -5 =-x+x -4 -5
e) 1-(t+p)-(t-2) = 1-t -p -t +2 = -t -t -p+1+2
f) -(-Y+2)+(-2Y-4)= y-2-2y-4 =y-2y-2-4= -3y-6
2010-03-27T14:06:04+01:00
A) a + a - b = 2a - b
b) 2x - x + 4 = x - 4
c) 7 - x - 6 = 1 - x
d) -x - 4 + x - 5 = -9
e) 1 - t - p - t + 2 = 3 - 2t - p
f) - y - 2 - 2y - 4 = -6 -3y

mam nadzieję, że dobrze. ^^